1036. Persistence of Guideline-Recommended Antiretroviral Therapy Regimens among Persons Living with HIV Newly Initiating Treatment in the US. (31st December 2020) - Cohen, Joshua P; Wang, Xingzhi; Wade, Rolin L; Cuervo, Helena Diaz; Dionne, Dionne M
Abstract: Background: Discontinuation of first-line antiretroviral therapy (ART) may lead to poor outcomes for persons living with HIV (PLWH). While single-tablet regimens (STRs) have been associated with greater persistence compared to multi-tablet regimens (MTRs), few real-world studies have assessed persistence with current guideline-recommended ART regimens. The study aims to assess persistence among treatment-naïve PLWH initiating guideline-recommended ART regimens Methods: Longitudinal pharmacy claims were extracted from IQVIA's US LRx database for PLWH initiating ART between Jan 1, 2016 - Jul 31, 2019 (index period), with the observational period up to Jan 31, 2020. Index date was defined as the date of the first ART claim for STRs, or the date of the last filled drug of 1 st set of claims for MTRs. Persistence was measured as the number of days until treatment discontinuation (≥ 90-day gap in therapy) and presented via Kaplan-Meier curves. Risk of discontinuation was assessed via Cox proportional hazards models, with BIC/FTC/TAF used as the reference ART regimen. Results: Overall, 90, 949 PLWH initiated STRs and 20, 737 initiated MTRs. Average (SD) age was 43 (14) years, 75% were male, and 75% had commercial insurance. At 6 months of follow-up, 71% of PLWH initiating STRs and 56% initiating MTRs remained on their ART regimen. The proportion remaining on their index regimen at 6 months of follow-up was 79% for BIC/FTC/TAF, 73% for EVG/COBI/FTC/TAF, 71% for DTG/ABC/3TC, 69% for DTG + FTC/TAF, 67% for EFV/FTC/TDF, 62% for EVG/COBI/FTC/TDF, and 38% for DTG + FTC/TDF. Risk of discontinuation was higher for MTRs compared to STRs (hazard ratio [HR]: 1.63, 95% CI: 1.61 - 1.66). Compared to the referent BIC/FTC/TAF, risk of discontinuation was higher for EVG/COBI/FTC/TAF (HR: 1.54, 95% CI: 1.48 - 1.60), DTG/ABC/3TC (HR: 1.58, 95% CI: 1.52, 1.65), DTG + FTC/TAF (HR: 1.83, 95% CI: 1.74 - 1.93), EFV/FTC/TDF (HR: 2.31, 95% CI: 2.21 - 2.41), EVG/COBI/FTC/TDF (HR: 2.58, 95% CI: 2.47 - 2.70), and DTG + FTC/TDF (HR: 6.20, 95% CI: 5.83 - 6.59). Table 1. Persistence with ART by regimen for STR and MTR Figure 1. Forest Plot of Hazard Ratios for Treatment Discontinuation Conclusion: Among US adult PLWH, STRs were associated with longer persistence on first-line therapy compared to MTRs. Among STRs, persistence was highest for BIC/FTC/TAF. Disclosures: All Authors : No reported disclosures